The Hong Kong version of the Oxford Cognitive Screen (HK-OCS): validation study for Cantonese-speaking chronic stroke survivors. Issue 5 (2nd September 2016) - Kong, Anthony Pak-Hin; Lam, Pinky Hiu-Ping; Ho, Diana Wai-Lam; Lau, Johnny King; Humphreys, Glyn W.; Riddoch, Jane; Weekes, Brendan
ABSTRACT: This study reports the validation of the Hong Kong version of Oxford Cognitive Screen (HK-OCS). Seventy Cantonese-speaking healthy individuals participated to establish normative data and 46 chronic stroke survivors were assessed using the HK-OCS, Albert's Test of Visual Neglect, short test of gestural production, and Hong Kong version of the following assessments: Western Aphasia Battery, MMSE, MoCA, Modified Barthel Index, and Lawton Instrumental Activities of Daily Living scale. The validity of the HK-OCS was appraised by the difference between the two participant groups. Neurologically unimpaired individuals performed significantly better than stroke survivors on the HK-OCS. Positive and significant correlations found between cognitive subtests in the HK-OCS and related assessments indicated good concurrent validity. Excellent intra-rater and inter-rater reliabilities, fair test–retest reliability, and acceptable internal consistency suggested that the HK-OCS had good reliability. Specific HK-OCS subtests including semantics, episodic memory, number writing, and orientation were the best predictors of functional outcomes.